If you can see the dark - Mudie, Timothy; Ward, Jenny (AMC); Templeton, Mattie Rose (Boston, MA : Appalachian Mountain Club, 2023)
"Moose, bats, fireflies, and all kinds of animals need the dark. From migration to finding each other to sleeping soundly, dark skies improve the lives of creatures great and small. Find out why dark skies are important for people, plants, and animals, and how to conserve them where you live. If you can see the dark, you can see so many amazing things." --back cover.
Maine author.
Maine author.
Keywords: Dark; Night; Sky; Nocturnal animals; Constellations; Stars; Fireflies; Moths; Sleep; Picture books